Differentiated Learning Model on Students’ Digital Literacy and Socioemotional Intelligence - Dewi, Kadek Yati Fitria; Kusuma, Kadek Hendra Adi; Puger, I Gusti Ngurah (Universitas Pendidikan Ganesha, 2025)
In classroom learning, many students have not achieved digital literacy and socioemotional intelligence optimally. This condition shows that conventional learning is not effective enough to support students' learning needs in a more diverse and holistic manner. Therefore, this study aims to evaluate the effect of differentiated learning model on students' digital literacy and socioemotional intelligence, and predict its effectiveness in improving both aspects. This research is quasi-experimental research with post-test only control group design. The research subjects were students in grade VIII, consisting of two groups, namely experimental and control groups, each totaling 32 students, making a total of 64 test subjects. Data were collected using the digital literacy questionnaire and socioemotional intelligence questionnaire as research instruments. Data analysis included t-test to see differences between groups and Product Moment Correlation test to strengthen variable relationships. The results showed that the differentiated learning model significantly improved students' digital literacy and significantly improved students' socioemotional intelligence compared to conventional learning. Thus, it is concluded that differentiated learning is able to optimize students' digital literacy skills and socioemotional intelligence, thus answering the problem of low mastery of these two competencies in the classroom. This research has implications for the importance of implementing differentiated learning in the current educational context to support student-centered learning and better prepare them to face the challenges of life.